Characterization of The Properties of South Lampung Clay as Lightweight Expanded Clay Aggregate - Anang Ansyori; , Adi Prasetyo; Tumpal Ojahan Rajagukguk; Beny Hartawan; Yusup Hendronursito (Journal of Science and Technology, 2025)
Bloating properties are essential to determine clay’s ability to expand and form pore structures for lightweight expanded clay (LECA) applications. South Lampung clay was taken from four different places: TN, TB1, TB2, and TJ. The clay was dried at 110oC until the water content was 7%, then ground using a ball mill to 200 mesh. The clay was formed into balls with a diameter of 10 mm and then heated at 1,050oC for 15 minutes. The chemical composition was analyzed by X-ray fluorescence. X-ray diffraction was used to analyze the crystal structure formed. Topography was analyzed using FESEM. The bloating coefficient (Cb) was calculated by comparing the volume before and after heating. Based on SiO2, TN and TB1 meet the self-bloating standard with 52.28 and 56.82% content, respectively. However, based on Al2O3, only TB1 meets the minimum standard with a value of 17.46%. Based on the total flux being below 10%, all clay has the potential for self-bloating. The type of clay is kaolinite with feldspar and kaolin phases. The bloated clay was found in TB1 and TJ with values ??of 1.08 and 1.46. Additives are needed to increase an expansion. This study can be developed to obtain the composition of local clay, which can be applied to various fields.